Hepatoprotective and Anti-Oxidant Study of Mukta Bhasma (Calx of Cultured Pearls) Against CCl4-Induced Hepatic Damage in Rats (In-Vivo).: Pharmaceutical Science- Ayurvedha - B.Tukanatti, Poornima; Jadar, Prashant; Vishwanath, Wasedar (International Journal of Life Science and Pharma Research, 2022)
Mukta Bhasma (MB) is a traditional Ayurvedic preparation for upper respiratory and lower respiratory conditions, eye disorders, powerful cardiac tonic, immune-regulator, mood elevator and known to promote strength, intellect and semen production. Mukta bhasma is prepared using direct heat as a media of transformation. Mukta Bhasma was evaluated for its hepatoprotective and antioxidant activities against Carbon tetrachloride (CCl4) induced liver damage in wistar albino rats. Mukta Bhasma (100mg/kg, 200mg/kg and 300mg/kg) was administered to experimental rats for 10 days. Silymarin (25mg/kg) was given as the standard drug. The hepatoprotective activity was assessed using various serum biochemical parameters like (SGOT), (SGPT), Total and Direct bilirubin (TB and DB), Alkaline phosphatase (ALP), Total Triglycerides (TG) and Total Cholesterol (TC). Lipid peroxidation (LPO), Reduced Glutathione (GSH) and Catalase (CAT) were determined to explain the antioxidant activity of Mukta Bhasma. The substantially elevated levels of SGOT, SGPT, TB and DB, ALP, TG and TC due to CCl4 treatment were restored towards near normal by Mukta bhasma (MB) of 200mg/kg dose. Administration of MB 200mg has shown significant reduction in the biochemical parameters like SGOT, SGPT, ALP, Bilirubin, Total cholesterol and Total triglycerides with significance of p<0.001 in all the parameters when compared to CCl4 group. Also, they were near to the standard Silymarin group. Mukta bhasma 200mg has shown significant (p<0.001) reduction in the LPO level, increase in CAT and GSH representing significant antioxidant activity of Mukta bhasma. The histopathological study showed reduction in fatty degeneration of liver in MB 200mg/kg body weight. Thus, results revealed that Mukta bhasma afford significant hepatoprotective and antioxidant effects in CCl4 induced hepatic damage.